Implementation of Dijkstra's Algorithm in Open Shortest Path First (OSPF) Routing Protocol Using Juniper - Fadhil Khanifan Achmad; Dadang Iskandar Mulyana; Yuma Akbar (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
In the modern era with the growth of human resources and the acceleration of the need for rapid communication, of course it must be accompanied by the development of network technology to support these needs, in this case network technology plays a very important role as a bridge to connect between nodes or individuals. but in practice it is often encountered in large-scale computer networks facing problems in data communication lines. the transmission process to distribute data takes a long time because of the wrong route selection. And in this case the OSPF (Open Shortesh Path First) routing protocol is here to be able to answer this problem, OSPF is a routing protocol that is often used in medium and large scale networks. OSPF distributes routing information between autonomous system (AS) routers. OSPF is a routing protocol that uses a linkstate algorithm to construct and calculate the best path to all known destinations. The link-state algorithm is also known as the dijkstra algorithm or the shortest path first (SPF) algorithm. The dijkstra algorithm is applied in the OSPF protocol to choose the best route that must be taken by a data packet from an origin address in order to arrive at the destination address with the smallest unit load value (cost/metric). Abstrak Bahasa Inggris maksimum 250 kata dalam satu alinea menggunakan huruf Arial 10, spasi 1. Abstrak berisi pendahuluan singkat, tujuan, metode dan hasil secara ringkas dan jelas. Penulisan singkatan yang tidak umum tidak diperkenankan kecuali didefinisikan sebelumnya.